Photo-induced alignment behaviour of polymerisable liquid crystals on bisazide in a polymer matrix. Issue 7 (27th May 2016) - Kimura, Yuki; Kuboyama, Keiichi; Ougizawa, Toshiaki
ABSTRACT: Photo-reactive bisazide in a polymer matrix containing acryloyl groups on the side chain was investigated as a photoalignment layer for polymerizable liquid crystals (PLC). We found the thin film of bisazide (2, 6-bis(4-azidobenzylidene)-4-methyl-1-cyclohexanone) in a polymer matrix, irradiated by linearly polarised ultraviolet light (LPUVL), was able to homogeneously align PLC. The LPUVL irradiation dose changed the orientation direction of the PLC on the thin film of bisazide in the polymer matrix. In addition, the direction of the slow axis for the retardation of the photoalignment layer changed from parallel to perpendicular to the LPUVL electric field with the irradiation dose. From these results, it was suggested that the PLC was likely to be aligned along the slow axis of the retardation of the photoalignment layer. We concluded that the key mechanism that changed the direction of the slow axis in a plane was the photoreaction of azide–acrylate at low irradiation dose and that of bis(benzylidene)cyclohexanone at high irradiation dose. Although the photoalignment as a result of a simple photo cross-linking was previously little known except for photo-dimerisation, we revealed that the photoaddition of azide–acrylate is able to achieve the photoalignment. GRAPHICAL ABSTRACT: